A systematic review of economic evaluations of interventions to tackle cardiovascular disease in low- and middle-income countries - Suhrcke, Marc (BioMed Central, 2012)
BACKGROUND: Low-and middle-income countries are facing both a mounting burden of cardiovascular disease (CVD) as well as severe resource constraints that keep them from emulating some of the extensive strategies pursued in high-income countries. There is thus an urgency to identify and implement those interventions that help reap the biggest reductions of the CVD burden, given low resource levels. What are the interventions to combat CVDs that represent good "value for money" in low-and middle-income countries? This study reviews the evidence-base on economic evaluations of interventions located in those countries. METHODS: We conducted a systematic literature review of journal articles published until 2009, based on a comprehensive key-word based search in generic and specialized electronic databases, accompanied by manual searches of expert databases. The search strategy consisted of freetext and MeSH terms related to economic evaluation and cardiovascular disease. Two independent reviewers verified fulfillment of inclusion criteria and extracted study characteristics. RESULTS: Thirty-three studies met the selection criteria. We find a growing research interest, in particular in most recent years, if from a very low baseline. Most interventions fall under the category primary prevention, as opposed to case management or secondary prevention. Across the spectrum of interventions, pharmaceutical strategies have been the predominant focus, and, taken at face value, these show significant positive economic evidence, specifically when compared to the counterfactual of no interventions. Only a few studies consider non-clinical interventions, at population level. Almost half of the studies have modelled the intervention effectiveness based on existing risk-factor information and effectiveness evidence from high-income countries. CONCLUSION: The cost-effectiveness evidence on CVD interventions in developing countries is growing, but remains scarce, and is biased towards pharmaceutical interventions. While the burden of cardiovascular disease is growing in these countries, future research should put greater emphasis on non-clinical interventions than has hitherto been the case. Significant differences in outcome measures and methodologies prohibit a direct ranking of the interventions by their degree of cost-effectiveness. Considerable caution should be exercised when transferring effectiveness estimates from developed countries for the purpose of modelling cost-effectiveness in developing countries. New local CVD risk factor and intervention follow-up studies are needed. Some pharmaceutical strategies appear cost-effective while clarifications are needed on the diagnostic approach in single high-risk factor vs. absolute risk targeting, the role of patient compliance, and the potential public health consequences of large-scale medicalization.